The origin and development of procedural rules in Ancient Greece - D. V. Slynko; L. I. Kalenichenko (Bulletin of Kharkiv National University of Internal Affairs)
The research is devoted to the development of legal norms in Greece in the ancient period. It is noted that certain issues of legal norms development in Greece in the ancient period were the subject of research by domestic lawyers and historians, but Ukrainian legal science currently lacks comprehensive historical and legal research on this issue which would cover the entire range of issues related to the origin and development of procedural law in Greece in the ancient period.